Pelaksanaan Ganti Rugi Akibat Pemasangan Tiang Listrik di Lahan Masyarakat di Kota Jambi - Nayu Triska Wulan Dari; Diana Rani; Retno Kusuma; Setly Selva Yuneida (Universitas Batanghari Jambi, 2025)
The issue of compensation for the installation of electricity poles on community land in Jambi City is a serious concern, because until now there has been no adequate compensation from PT. PLN (Persero) UP3 Jambi. Residents who own land are questioning their rights regarding the use of private assets for public interests and settlement mechanisms in accordance with regulations. This ambiguity has the potential to cause dissatisfaction, so a solution needs to be found immediately to fulfill community rights. This study uses a socio-legal research approach with an activity plan of three months so that the scope or object of the study is the implementation of compensation due to the installation of electricity poles on community land in Jambi City. For this reason, the main materials and tools are direct research in the Jambi City community and secondary data are books and Law Number 30 of 2009 concerning Electricity. The data collection technique is in the form of interviews so that the data analysis uses qualitative analysis methods. The results of this study are that the regulation of compensation due to the installation of electricity poles on community land has been regulated in Article 30 of Law Number 30 of 2009 concerning Electricity and the implementation of compensation due to the installation of electricity poles on community land in Jambi City has not been implemented compensation to the people of Jambi City related to their land used for the installation of electricity poles by PT. PLN (Persero) UP3 Jambi.